On-chain witness and off-chain transmission trustworthy data sharing platform - Zhao ZHANG; Jixin TIAN; Cheqing JIN (大数据)
Blockchain system can build a trusted infrastructure for sharing data between multiple untrusted parties.However,directly uploading original shared data to blockchain is not suitable for large-scale data sharing scenarios.A data sharing architecture where data sharing request and response records are deposited on-chain and original data is transmitted securely off-chain was proposed.The architecture can alleviate the problems of system overload and privacy protection to a certain extent.Finally,with the increase of participating nodes and the data sharing requests and responses to be handled per second,the limitations in distributed storage,consensus protocol,smart contract execution,and query from light clients,directions for further research were proposed,in order to specify the technical bottlenecks that need to be further broken for the existing blockchain system applied to the field of data sharing.